(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Household CO_2 emissions are gaining more attention from researchers in recent years. Domestic washing is an important household routine and one of the main sources of household CO_2 emissions. In this paper, Consumer Lifestyle Approach (CLA) was used to quantify CO_2 emissions from domestic washing. An investigation of 493 families, from 16 cities out of 8 provinces in China, was held to study the five main household characteristics including the demographic composition, living condition, family income and expenditure, education level and most importantly, laundry habit. The relationship between domestic washing characteristics and CO_2 emissions is concluded from multi-variable linear return analysis. The results show that family's washing frequency as well as washing machine's efficiency and capacity are major factors which affect CO_2 emissions. Other factors such as per capita living space, family working population and education level also have an influence to a certain extent.